Evaluasi Pelayanan Geriatri Berdasarkan Standar Akreditasi Kemenkes RI (STARKES) di Rumah Sakit Yarsi Tahun 2025 - Fratiwi, Linda; Nugroho, Dedy; Satar, Yuli Prapanca (Jurnal Manajemen dan Administrasi Rumah Sakit Indonesia (MARSI), 2025)
The increasing elderly population in Indonesia demands high-quality geriatric care in accordance with the accreditation standards set by the Ministry of Health of the Republic of Indonesia. RS YARSI, as one of the hospitals providing geriatric services, needs to evaluate the implementation of accreditation standards to ensure optimal service quality. This study aims to evaluate the implementation of geriatric services at RS YARSI based on the Ministry of Health Accreditation Standards (STARKES), identify barriers, and provide recommendations for improving the quality of geriatric care. The research employs a qualitative approach using in-depth interviews, Focus Group Discussions (FGD), observations, and document reviews, with analysis based on the Input-Process-Output evaluation model to assess compliance with accreditation standards. Gap analysis results indicate that RS YARSI has met the standards in terms of regulations, geriatric teams, education, and funding. However, deficiencies remain in regulatory updates, workforce readiness, independent care facilities, elderly education methods, and the digitization of reporting and evaluation. With a compliance level of 60-70%, RS YARSI is categorized under the COMPLETE service level but has not yet reached the ADVANCED EXCELLENT level. To achieve the highest standard of geriatric care, RS YARSI needs to update internal regulations, enhance the number of certified geriatric healthcare professionals, strengthen independent care facilities, digitize reporting and evaluation systems, and optimize interprofessional coordination. Implementing these strategies will support full accreditation achievement and comprehensively improve the quality of geriatric services.